Analysis by Metabolomics and Transcriptomics for the Energy Metabolism Disorder and the Aryl Hydrocarbon Receptor Activation in Male Reproduction of Mice and GC-2spd Cells Exposed to PM2.5 - Shi, Fuquan; Zhang, Zhonghao; Wang, Jiankang; Wang, Yimeng; Deng, Jiuyang; Zeng, Yingfei; Zou, Peng; Ling, Xi; Han, Fei; Liu, Jinyi; Ao, Lin; Cao, Jia (Frontiers in Endocrinology, 2022)
Fine particulate matter (PM2.5)-induced male reproductive toxicity arouses global public health concerns. However, the mechanisms of toxicity remain unclear. This study aimed to further investigated toxicity pathways by exposure to PM2.5 in vitro and in vivo through the application of metabolomics and transcriptomics. In vitro, spermatocyte-derived GC-2spd cells were treated with 0, 25, 50, 100 μg/mL PM2.5 for 48h. In vivo, the real-world PM2.5 exposure mouse model was established. Forty-five male C57BL/6 mice were exposed to filtered air, unfiltered air and concentrated ambient PM2.5 in Tangshan of China for 8 weeks, respectively. The results in vitro and in vivo showed that PM2.5 exposure inhibited GC-2spd cell proliferation and reduced sperm motility. After treatment with PM2.5, the mitochondrial damage was observed, and Increased Humanin and MOTS-c level and mitochondrial respiratory depression indicated that mitochondrial function was disturbed. Furthermore, nontargeted metabolomics analysis revealed that PM2.5 exposure can disturber citrate cycle (TCA cycle) and reduce amino acids and nucleotide synthesis. In addition, the aryl hydrocarbon receptor (AhR) pathway was activated and the expression of CYP1A1 was significantly increased after exposure to PM2.5. Moreover, PM2.5 exposure significantly increased both intracellular and mitochondrial reactive oxygen species (ROS) and activated NRF2 antioxidative pathway. With RNA-sequencing technique, the differentially expressed genes induced by PM2.5 exposure were mainly enriched in the metabolism of xenobiotics by cytochrome P450 pathway, and Cyp1a1 was the most significantly changed gene. Our findings demonstrated that PM2.5 exposure can induce Spermatocyte damage, and energy metabolism disorder and activation of the aryl hydrocarbon receptor may be involved in the mechanisms of male reproductive toxicity.